GENRE FEATURES IN THE WORK OF T.KAYIPBERGENOV «QALBIMNIN QAMUSI» - Matimov, K.G. (SCIENCE and SOCIETY, 2026)
The article discusses T.Qayipbergenov's work during the independence period, particularly the writer's work «Qalbimning qamusi» (Word of My Heart), with its unique genre and composition. Thus, the author explores the transformation of the novel-essay genre into a tradition in his work and provides a scholarly and theoretical overview of this genre.
Keywords: novel-essay; essay writing; essay; genre transformation; reportage-essay; «Qalbimning qamusi»; religious-philosophical work